Leishmaniose visceral - Bracarense, Carolina Braga; Mesquita, Lucas de Oliveira; Antunes, Lucca Piuzana; Oliveira, Sarah dos Santos; Alvarenga, Janaina Sousa Campos; Alvarenga, Ângela Cardoso (Seven Editora, 2024)
Introduction: Visceral Leishmaniasis is a parasitic disease transmitted by sandflies, causing fever, weight loss and inflammation of the spleen. Identified in 1903, its global spread is influenced by socioeconomic and environmental factors. The parasites responsible for this disease are trypanosomatid protozoa that belong to the genus Leishmania. The vectors are sandflies, mainly of the species Lutzomyia longipalpis infected by Leishmania chagasi. Popularly known as sand flies, they reproduce in areas rich in organic matter. The evolutionary cycle of Leishmania chagasi is heteroxenic, involving vertebrate hosts such as canids, marsupials or humans, and invertebrate hosts, which are sandfly insects. Initially, Visceral Leishmaniasis may be asymptomatic or present with prolonged fever, weight loss, weakness, and anemia. Then, symptoms such as enlargement of the spleen and liver, pallor, intermittent fever and impairment of the immune system appear. In the advanced stage of infection, serious complications such as hemorrhages, secondary infections, profound anemia, and hepatosplenic insufficiency occur. The diagnosis of Visceral Leishmaniasis involves a series of clinical, laboratory and epidemiological approaches. The treatment of Visceral Leishmaniasis in Brazil is done with pentavalent antimonial compounds, such as the antimoniate N-methyl glucamine, administered intravenously or intramuscularly. Some contraindications include renal or hepatic failure, pregnancy in the first two trimesters, and patients taking beta-blockers or antiarrhythmics. Preventive measures must be carried out in individual and collective environments. These measures include the use of repellents, avoiding exposure at times when the vectors are most active, environmental management, tree pruning, cleaning of pet shelters, among others. Visceral Leishmaniasis represents a complex public health challenge. Understanding the protozoan cycle, diagnostic methods, and treatment options is crucial for effective disease management. DOI:https://doi.org/10.56238/sevened2024.016-004